2006
DOI: 10.1093/nar/gkj447
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of geminivirus-derived small RNAs in different plant species

Abstract: DNA geminiviruses are thought to be targets of RNA silencing. Here, we characterize small interfering (si) RNAs—the hallmarks of silencing—associated with Cabbage leaf curl begomovirus in Arabidopsis and African cassava mosaic begomovirus in Nicotiana benthamiana and cassava. We detected 21, 22 and 24 nt siRNAs of both polarities, derived from both the coding and the intergenic regions of these geminiviruses. Genetic evidence showed that all the 24 nt and a substantial fraction of the 22 nt viral siRNAs are ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
184
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(200 citation statements)
references
References 54 publications
13
184
0
3
Order By: Relevance
“…The profile of ⌬CP-specific siRNAs is generally consistent with previous reports (6,9,17). Their size was predominantly 21 nt in all but the dcl4 plants, where the DCL2-generated 22-nt siRNA predominates (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The profile of ⌬CP-specific siRNAs is generally consistent with previous reports (6,9,17). Their size was predominantly 21 nt in all but the dcl4 plants, where the DCL2-generated 22-nt siRNA predominates (Fig.…”
Section: Resultssupporting
confidence: 90%
“…In addition to the endogenous siRNAs, viruses and transgenes also give rise to siRNAs (reviewed in Brodersen and Voinnet, 2006;Vaucheret, 2006). We and others have shown that all types of siRNAs (except nat-siRNAs that have not been tested) are methylated in vivo in a HEN1-dependent manner (Akbergenov et al, 2006;Ebhardt et al, 2005;Li et al, 2005). Our biochemical studies with recombinant HEN1 protein also demonstrated that HEN1 is a siRNA methyltransferase (Yang et al, 2006).…”
Section: Introductionsupporting
confidence: 54%
“…Recent studies show that infections by ssDNA geminiviruses trigger accumulation of different vsRNA classes (14). This likely reflects the action of distinct DCLs that possibly use dsRNA resulting from annealing of converging sense͞antisense transcripts as substrate (15).…”
mentioning
confidence: 99%